Verbrechen und Strafe in der jüdischen Rechtstradition - Pekárek, Hendrik (Schriften zur Rechtsgeschichte, 2021)
»Crime and Punishment in the Jewish Legal Tradition«: In his book, Hendrik Pekárek explores the development of penal law and criminal procedure in the Jewish legal tradition, the Halacha, under literary, legal historical and comparative law aspects. Using narratives and legal sources from the Torah, Midrash and Talmud, medieval codifications and legal opinions, he vividly traces the unfolding of legal concepts throughout three millennia and illustrates their impact on the life of Jewish communities until modern times.